Cyrtodactylus madarensis Sharma (1980), a junior synonym of Eublepharis macularius Blyth (1854) - Das, Indraneil (Asiatic Herpetological Research Society, 1992)
Cyrtodactylus madarensis was described by Sharma (1980) based on a single juvenile male from near Madar (alt. 263 m), approximately 5 km north-west of Ajmer City, Rajasthan, in north-western India. No diagnosis of the new species was provided and the author compared his new find, for reasons uncited, only with the gekkonid, Cyrtodactylus stoliczkai, which is restricted to the extreme northern parts of India (Kashmir and Ladakh) and northwestern Pakistan (North-West Frontier Province) and adjacent China (Welch et al., 1990).